Akulturasi Islam dan Tradisi Lokal Kosek ponjen pada Upacara Pernikahan Masyarakat Osing - Wiwik Setiyani; Zakkiyatul Fikriyah; Nasruddin Nasruddin (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
Kosek ponjen is a marriage tradition among Osing society in Banyuwangi. It’s interesting to examine the Osing society’s believe that this tradition becomes a way to cleanse the groom and bride from various dangers. The groom or bride exclusively performs this ritual if they happened to be their family's youngest son or daughter. This article explains the intersection between Islam and kosek ponjen local tradition during marriage ceremonies. Qualitative research method applies in-depth interview to obtain comprehensive data regarding the marriage ritual. Kosek ponjen could be analyzed using Victor Turner’s symbolic meaning theory. This research finds that Osing society implements kosek ponjen as a compulsory ritual during marriage to symbolize an exchange between the parents and the groom and bride to throw upcoming misfortunes away. Symbols being used include rice grains, coins and a carrying pole with an important message for the family. The groom and bride need to trust each other and tolerate each other’s shortcomings, seek their parents’ acknowledgement and believe in Allah that their family will be harmonious for the rest of their life. Acculturation between Islam and local marriage tradition in Banyuwangi formed a diverse culture rich in moral values in starting a family.